Development of Contextual Teaching and Learning System (CTL) in Improving the Skills of Internal Auditor Candidates: A Bibliometric Analysis Based on Scopus, Web of Science, and Dimensions (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
This study examines the trends of publications, authors, and main topics related to contextual learning in improving the skills of prospective internal auditors through bibliometric analysis. Using data from Scopus, Web of Science, and Dimensions, this study analyzed the literature with VOSviewer and Bibliometrix. The results show a significant increase in research on contextual learning since 2018, with the largest contribution from the United States, the United Kingdom, and Australia, as well as an increase from Indonesia. Dominant keywords such as teaching, learning, and skills underscore the importance of integrating theory and practice in auditor education. The co-citation analysis identified seminal works such as Liu Y. (2018) and Bretag T. (2019). The study recommends further development in the use of advanced technologies such as virtual simulations and AI to improve the skills of aspiring auditors as well as collaboration between education and industry.